Body-Worn Cameras: Reducing Citizen Complaints and Improving Relationships - Bui, Julie (2017)
Video recordings of police-citizen interactions, most notably those obtained from the dashboard cameras (dashcams) of police cars, have been successful in objectively capturing police-citizen exchanges. However, since police-civilian interactions do not solely occur in front of police cars, dashcams present significant limitations. Off-camera violent, and sometimes fatal, encounters (such as the notorious Ferguson case) have fueled increased public support for body-worn cameras. This is especially true in cases with conflicting accounts from the officer(s), victim(s), and witness(es). Requiring officers to wear bodycams may reduce incidents of force and citizen complaints, and increase officer accountability. This paper will present peer-reviewed research to help create an understanding of officer perceptions about the device, and will evaluate the effects of bodycams on both police officers and the communities they serve. Although bodycams have the potential to improve behaviors of both officers and civilians, its efficacy is dependent on its implementation (i.e., policies). Additionally, this paper will present suggestions for police agencies adopting the use of bodycams. Since bodycams hold promise for helping to rebuild relations between officers and the community, more research and feedback can help address the growing privacy and retention concerns